Geographic susceptibility of Helicoverpa armigera (Lepidoptera: Noctuidae) to insecticidal proteins in Bt-cotton in South Africa - Van Jaarsveld, Martha Johanna (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2004)
Helicoverpa armigera Hübner (Lepidoptera: Noctuidae) (African bollworm) is a typical noctuid with a very catholic taste in food plants and whose larvae feed on a wide range of cultivated and wild plants. It has been identified as the most polyphagous and injurious pest in South Africa. Helicoverpa armigera is also a key pest of cotton in many parts of the world. This key pest requires extensive control as it adversely effects yield and has built up resistance to synthetic pyrethroid insecticides. Cotton is an important crop produced by commercial and small-scale farmers in South Africa. The local demand for cotton has not been exceeded yet, but to satisfy a demanding market, pest control costs play an important role in cotton production. The threat of an insect pest that has already shown resistance prompted the present study to investigate the possibility of resistance to Bt-cotton. Genetically engineered or Bt-cotton was introduced commercially in 1996 in South Africa. All Bt-cotton plants contain one or more foreign genes derived from the soil-dwelling bacterium, Bacillus thuringiensis (Berliner), which produces protein crystals. These crystals were isolated and transferred into the genome of a cotton plant resulting in the plant producing it's own protein insecticide. In 1998, Monsanto (Pty) Ltd requested research into the geographic susceptibility of H. armigera to the insecticidal proteins in Bt-cotton in SA. Laboratory reared and field sampled populations of H. armigera were exposed to a diet mixed with various baseline concentrations of the Bt-gene Cry1Ac freeze dried protein. This study also determined the performance of H. armigera and Spodoptera littoralis (Boisduval) on different Bt-cotton field cultivars containing different Cry-protein genes. Results obtained indicated a significant difference in susceptibility in two field populations of H. armigera to the Bt-protein Cry1Ac, even though the LD50,s in the 2003 season did not indicate resistance. Bt-cotton cultivar 15985 BX controlled H. armigera and S. littoralis larvae, the best followed in descending order by cultivar 15985 X, 15985 B and DP50 B. Results on H. armigera also indicated that the Cry-proteins in the plant parts of the different cultivars did not diminish as the season progressed. The Bt-cotton cultivars induced retarded growth of larvae, due to either a repellent effect or lack of feeding by larvae. Widespread adoption of Bt-cotton by South African farmers led to regional declines in bollworm populations, reduced insecticide use, and increased yields. Genetically modified crops therefore contribute to a cost effective, sustainable, productive and efficient form of agriculture, with a resultant positive impact on the environment. As the market for commercial Bt-cotton in South Africa expands, it is recommended that a monitoring programme for potential resistant genes in H. armigera should be implemented at least every 2 - 3 years. This will ensure that effective resistance management strategies are utilised. Coupled with this are the Biosafety Risks regarding the effect of new proteins expressed in transgenic plants, which require further studies.
Keywords: Helicoverpa armigera; Noctuidae; Lepidoptera; Cotton -- Diseases and pests -- South Africa